Correction: The effect of light wavelength on in vitro bilirubin photodegradation and photoisomer production - Vreman, Hendrik J; Kourula, Stephanie; Jašprová, Jana; Ludvíková, Lucie; Klán, Petr; Muchová, Lucie; Vítek, Libor; Cline, Benjamin K; Wong, Ronald J; Stevenson, David K (Pediatric research, 2019)
Following publication of this article, the authors noticed that an incorrect affiliation was assigned to the author "Lucie Muchová". The original article has now been updated so that the author "Lucie Muchová" is associated with the "Institute of Medical Biochemistry and Laboratory Diagnostics, 1st Faculty of Medicine, Charles University, Kateřinská 32, 120 00 Prague, Czech Republic". This has been corrected in both the PDF and HTML versions of the article.